Spidroin profiling of cribellate spiders provides insight into the evolution of spider prey capture strategies - Kono, Nobuaki; Nakamura, Hiroyuki; Mori, Masaru; Tomita, Masaru; Arakawa, Kazuharu (Scientific reports, 2020)
Orb-weaving spiders have two main methods of prey capture: cribellate spiders use dry, sticky capture threads, and ecribellate spiders use viscid glue droplets. Predation behaviour is a major evolutionary driving force, and it is important on spider phylogeny whether the cribellate and ecribellate spiders each evolved the orb architecture independently or both strategies were derived from an ancient orb web. These hypotheses have been discussed based on behavioural and morphological characteristics, with little discussion on this subject from the perspective of molecular materials of orb web, since there is little information about cribellate spider-associated spidroin genes. Here, we present in detail a spidroin catalogue of six uloborid species of cribellate orb-weaving spiders, including cribellate and pseudoflagelliform spidroins, with transcriptome assembly complemented with long read sequencing, where silk composition is confirmed by proteomics. Comparative analysis across families (Araneidae and Uloboridae) shows that the gene architecture, repetitive domains, and amino acid frequencies of the orb web constituting silk proteins are similar among orb-weaving spiders regardless of the prey capture strategy. Notably, the fact that there is a difference only in the prey capture thread proteins strongly supports the monophyletic origin of the orb web.